Study Of The Properties Of Dyed Silk And Cotton-Silk Fabrics From Chitosan-Based Compositions (Eurasian Journal of Engineering and Technology, 2022)
The results of studying the possibilities of textile auxiliary substances of chitosan for intensifying the process of dyeing silk and mixed fabrics with active dyes are presented. The article proposes the chemistry of the interaction and the nature of the bonds in the fiber - chitosan - dye system, investigated the effect of the concentration of intensifiers on the degree and amount of fixation of active dyes on the fiber.